Physicochemical characteristics and sensory evaluation of ‘kuih bangkit’ made from banana starch / Ayeesha Ahmad Mustaza - Ahmad Mustaza, Ayeesha (Faculty of Applied Sciences, 2008)
Interest in nutraceutical food has increase in consumer demands such as high fiber food products. However, addition or substitution of the ingredient gives several differences in taste, appearance, color and texture to the products. The objective of this final year project is to developed ‘Kuih Bangkit’, by substituting tapioca starch as the main ingredient with banana starch from different types of unripe banana such as ‘Pisang Rastali’, ‘Pisang Berangan’, ‘Pisang Nangka’. The study involved sensory analysis to determine the best formulation of cookies among the three types of banana. Besides that, chemical analysis was conducted to determine the proximate analysis between cookies from tapioca starch which was the control and the best cookies from banana starch. The effect of this substitution on the cookies was also determined by measuring the fracturability. From the analysis conducted, the best formulation which was most preferred by the panelist was cookies which were substituted with 50% of ‘Nangka’ banana starch with the mean value of 7.60. Proximate composition studies showed that cookies from banana starch contained 44.9% crude fiber, 33.7% carbohydrate, 16.4% fat, 2.4% protein, 2.0% moisture, and 0.6% ash. While control cookies contained 43.6% crude fiber, 34.0% carbohydrate17.7% fat, 3.0% moisture, 1.4% protein and 0.25% ash. From the texture analysis, control cookies required 744.67g force while cookies from banana starch required 1150.67g to fracture.